2012
DOI: 10.1111/j.1467-8624.2012.01815.x
|View full text |Cite
|
Sign up to set email alerts
|

Number‐Concept Acquisition and General Vocabulary Development

Abstract: How is number-concept acquisition related to overall language development? Experiments 1 and 2 measured number-word knowledge and general vocabulary in a total of 59 children, ages 30 to 60 months. A strong correlation was found between number-word knowledge and vocabulary, independent of the child’s age, contrary to previous results (Ansari et al., 2003). This result calls into question arguments that (a) the number-concept creation process is scaffolded mainly by visuo-spatial development, and (b) that langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 29 publications
10
90
0
3
Order By: Relevance
“…Children acquire the concept faster if they know more words, even if those words are in no way related to the numbers (Negen and Sarnecka, 2012). This evidence supports the above argument.…”
Section: An Empirical Reason For Conceptual Autonomysupporting
confidence: 83%
“…Children acquire the concept faster if they know more words, even if those words are in no way related to the numbers (Negen and Sarnecka, 2012). This evidence supports the above argument.…”
Section: An Empirical Reason For Conceptual Autonomysupporting
confidence: 83%
“…A strong correlation between the child's vocabulary and the knowledge of number words was found in a study by Negen and Sarnecka (2012).…”
Section: Cardinalitymentioning
confidence: 97%
“…Negen & Sarnecka, 2012) indicate the expressive vocabulary as an important predictor for numerical competence. Negen and Sarnecka (2012) also found an important correlation between the child's vocabulary and the knowledge of number words. The expressive vocabulary is the best linguistic predictor for mathematic competencies.…”
Section: Vocabulary and Phonological Awarenessmentioning
confidence: 99%
“…Of course, different children reach this milestone at different times, but in a sample of cardinal principle sometime between 34 and 51 months old. That is, any time from a couple of months before their third birthday to a couple of months after their fourth birthday (Negen & Sarnecka, 2012;Sarnecka & Carey, 2008;Sarnecka & Gelman, 2004;Sarnecka et al, 2007;Sarnecka & Lee, 2009;Slusser et al, 2013;Slusser & Sarnecka, 2011). Children from lowerincome backgrounds come to understand cardinality significantly later, at age 4 or older (Fluck & Henderson, 1996;Jordan & Levine, 2009).…”
Section: Acquiring a System Of Representation For Exact Numbersmentioning
confidence: 99%
“…Studies using the Give-N task have shown that children's performance moves through a predictable series of levels, called number-knower levels (e.g., Condry & Spelke, 2008;Le Corre & Carey, 2007;Le Corre et al, 2006;Negen & Sarnecka, 2012;Sarnecka & Gelman, 2004;Sarnecka & Lee, 2009Slusser, Ditta, & Sarnecka, 2013;Slusser & Sarnecka, 2011;Wynn, 1990Wynn, , 1992b. These number-knower levels are found in children acquiring number systems not only in English, but also in Arabic, Japanese, Mandarin Chinese, Russian, Slovenian, and even among the Tsimane', a farming and foraging society in rural Bolivia (Almoammer et al, 2013;Barner, Libenson, Cheung, & Takasaki, 2009;Li, Le Corre, Shui, Jia, & Carey, 2003;Piantadosi, Jara-Ettinger, & Gibson, 2014;Sarnecka, Kamenskaya, Yamana, Ogura, & Yudovina, 2007).…”
Section: Acquiring a System Of Representation For Exact Numbersmentioning
confidence: 99%